Macrophage Clearance of Apoptotic Cells: A Critical Assessment - Gordon, Siamon; Plüddemann, Annette (Frontiers in Immunology, 2018)
ABSTRACT. As the body continues to grow and age, it becomes essential to maintain a balance between living and dying cells. Macrophages and Dendritic cells play a central role in discriminating among viable, apoptotic and necrotic cells, as selective and efficient phagocytes, without inducing inappropriate inflammation or immune responses. A great deal has been learnt concerning clearance receptors for modified and non-self ligands on potential targets, mediating their eventual uptake, disposal and replacement. In this essay, we assess current understanding of the phagocytic recognition of apoptotic cells within their tissue environment; we conclude that efferocytosis constitutes a more complex process than simply removal of corpses, with regulatory interactions between the target and effector cells, which determine the outcome of this homeostatic process. INTRODUCTION Programmed cell death, apoptosis, is closely linked to recognition and clearance by phagocytosis, resulting in anti-inflammatory and compensatory growth responses during foetal and adult life. Prolonged or incomplete containment and destruction during the apoptotic process can merge into secondary necrosis to bring about pro-inflammatory and pathological responses by phagocytes that are still poorly understood. Many aspects of this process are covered in excellent reviews by leading investigators, including Henson (1), Ravichandran (2), Nagata (3), Grinstein (4) and their colleagues, which should be consulted for detailed exposition. We have previously reviewed the process of phagocytosis in relation to infection and microbial recognition (5), emphasising its cell biology in model systems.We focus here on clearance of apoptotic cells in situ by heterogeneous tissue mononuclear phagocytes, in health and disease.